Meningkatkan Kesadaran dan Partisipasi Masyarakat dalam Pengelolaan Sampah Berkelanjutan melalui Program Kerja Bak Pemilahan Sampah di Pantai Baru Nusantara - Devi, Suheriah Mulia; Abna, Fabio Bintang Azriel; Bagaskara, Gilang Arief (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Waste management in the Pantai Baru Nusantara area, Nenang Village, Penajam Paser Utara Regency, remains suboptimal, as some residents have not yet sorted their waste and mixed waste disposal practices persist. This community service activity aims to raise public awareness of waste management through a program to construct and install waste sorting bins. The method used is a participatory approach, encompassing permitting, problem identification, planning, construction, installation, and program evaluation. The results indicate that the waste sorting bins help residents and beach visitors separate waste by type: organic, inorganic, and light hazardous materials. The beach environment is cleaner, tidier, and more organized. This program has had a positive impact in raising public awareness of the importance of better and more sustainable waste management.